2018
DOI: 10.1016/j.ijpharm.2017.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of gefitinib-releasing polyurethane foam as a coating for drug-eluting stent in the treatment of bronchotracheal cancer

Abstract: The purpose of the present study was to develop gefitinib-loaded polymeric foams that can be used as coating of drug-eluting stents for palliative treatment of bronchotracheal cancer. Release of such an anticancer drug from such stent coating can retard tumor regrowth into the bronchial lumen. Gefitinib-loaded polyurethane (PU) foams were prepared by embedding either gefitinib micronized crystals or gefitinib-loaded poly(lactic-co-glycolic acid) microspheres in water-blown films, with up to 10% w/w loading for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 18 publications
3
8
0
Order By: Relevance
“…Several diffraction peaks are clear in the diffractogram of ZD at 15.1°, 16.1°, 18.6°, 19.2°, 20.6°, 22.5°, 24.2°26.2°and 26.4°. Similar peaks were reported in previous study which were attributed to drug crystallinity (27). PVP, HPMC and Eudragit S100 showed no sharp peaks in their diffractograms which is attributed to their availability in the amorphous form.…”
Section: X-ray Diffractometrysupporting
confidence: 88%
“…Several diffraction peaks are clear in the diffractogram of ZD at 15.1°, 16.1°, 18.6°, 19.2°, 20.6°, 22.5°, 24.2°26.2°and 26.4°. Similar peaks were reported in previous study which were attributed to drug crystallinity (27). PVP, HPMC and Eudragit S100 showed no sharp peaks in their diffractograms which is attributed to their availability in the amorphous form.…”
Section: X-ray Diffractometrysupporting
confidence: 88%
“…Drug-release studies showed a sustained highly controlled release of GEF over nine months (with zero-order kinetics). The developed biomaterial is dedicated for the palliative treatment of bronchotracheal cancer [ 70 ]. Another fascinating DDS with very high cytostatic (PACL) release control for 10 days is temperature-responsive PUs (obtained from MDI, PCL, and BDO) [ 71 ].…”
Section: Anti-cancer Drug Delivery Systems Obtained From Non-biodegra...mentioning
confidence: 99%
“…In Figure 6a, a broad peak at 3600-3200 cm -1 (stretching vibration of O-H) and peaks at 2920 cm -1 (asymmetric stretching vibration of C-H), 2870 cm -1 (symmetric stretching In Figure 6a, a broad peak at 3600-3200 cm −1 (stretching vibration of O-H) and peaks at 2920 cm −1 (asymmetric stretching vibration of C-H), 2870 cm −1 (symmetric stretching vibration of C-H), and 1100 cm −1 (C-O-C) belong to the EFB polyol. Common peaks that represent functionalities of urethanes and ureas in PU, such as a broad peak at 3300 cm −1 (stretching vibration of amine (N-H) in urethane linkages); peaks at 1720 cm −1 (free C=O of urethanes), 1705 cm −1 (H-bonded C=O of urethanes), 1595 cm −1 (aromatic group of p-MDI), 1510 cm −1 (bending vibration of N-H), 1415 cm −1 (isocyanurate ring), 1360 cm −1 (aromatic amine C−N stretching from p-MDI) [38], 1215 cm −1 (stretching vibration of C-N in urethane linkages) [27], and 1080 cm −1 (C-O-C of urethanes); and a shoulder peak at 1650 cm −1 (N-H of urea) [39] are present in all EFBPUFs spectra.…”
Section: Ftir Analysismentioning
confidence: 99%